Experimental investigation on fatigue behaviour of glass/epoxy quasi-isotropic laminate composites under different ageing conditions. (February 2021) - Padmaraj, N.H.; Vijaya, Kini M.; Dayananda, Pai
Highlights: Investigations of fatigue behaviour of aged glass/epoxy quasi-isotropic laminates. Ageing of laminates in ambient, sub-zero and humid environments. Analysis of damage growth mechanism of laminates by monitoring residual stiffness. Fatigue life and damage growth rate of the laminates influenced by ageing environments. Abstract: The present work investigates the effect of ageing on fatigue performance of glass/epoxy quasi-isotropic laminates. Specimens were aged in artificial seawater at ambient, sub-zero and humid conditions for a period of 180 days. Static tensile and dynamic tension-tension fatigue tests were performed on pristine and aged specimens and based on the experimental results S-N curve, rate of stiffness degradation and damage accumulation were established. The results revealed that fatigue damage growth depends upon the ageing conditions and percentage of moisture content. Multiple cracks, interfiber debonding and matrix decomposition from the fibre surface are responsible for the deterioration of fatigue properties.